Numerical simulations of installation effects caused by upstream elbows on single-path transit-time ultrasonic flare flow meters - Martins, Ramon Silva (2012)
Oil and gas industry requires accurate flow measurements since they are stated by law. Nev-ertheless, curves and other obstacles are commonly found in such industry field, which mayaffect the quality of flow measurement due to flow disturbances, such as swirl and velocity pro-file asymmetries. Single-path ultrasonic flow meters are often used in flare gas installations,despite being sensitive to such disturbances. The present work use commercial CFD codes toobtain disturbed flow fields downstream from single and double elbow pipe installations, aimingto investigate both magnitude and behaviour of such effects on ultrasonic flow measurement.Numerical integration is applied for several acoustic path arrangements, simulating single-pathultrasonic flow meters in different situations in order to evaluate its correction factor devia-tion under disturbed conditions. Reynolds numbers from1×104to2×106are considered.Transducers mounting angles from 0° to 180° are tested and axial positions up to 80D down-stream from the curve are evaluated. Results indicate that single-path ultrasonic flow meters aresensitive to installation effects. Correction factor deviations usually showed to be significantlyhigher than 2% for axial positions shorter than 20D, as recommended by several manufactur-ers or regulations. Nevertheless, deviations may reach 0.01% in some specific configurations,which suggests that ultrasonic flow measurement might be improved by rearranging flow meterdevice in favourable angular position and mainly by implementation of specific functions forcorrection factors under disturbed conditions